NEW CALCAREOUS NANNOFOSSIL DATA ON THE CRETACEOUS-EOCENE AGE OF CORSICAN TURBIDITES - MARIA MARINO; SIMONETTA MONECHI; GIANFRANCO PRINCIPI (Rivista Italiana di Paleontologia e Stratigrafia, 2017)
A  detailed  biostratigraphical  study  based on  calcareous nannofossils  has been carried out on  the following Cretaceous-Eocene  flysch of Alpine Corsica:  Macinaggio Flysch, Tralonca  Flysch,  Vezzani Flysch,  Balagne Calcareous  Flysch,  Lydienne  (Toccone  Unit), Palasca  Sandstones,  Gare  de Novella Sandstones,  Alturaia  Arkoses. The bad preservation  of calcareous  nannofloras  due to dissolution and overgrowth  phenomena,  did not permit the recognition of precise biozonal  intervals; although many samples were barren, calcareous  nannofossils provided  further  information  about  the Corsican flysch age and they  often confirmed the previous age  determination  based  on Foraminifera. The Macinaggio Flysch, ascribed in  literature  to  the Cenomanian, has  been  referred  to an age  not older than  latest  Coniacian;  the Balagne  Calcareous  Flysch, previously  referred  to the Eocene  and, subsequently,  to the Senonian,  is Cenomanian and latest Coniacian-Campanian  in age; for the Palasca Sandstones the Eocene age has been confirmed; the Lydienne (Toccone  Unit) has  been referred  to an age  not older than  Late Albian; in the Gare de Novella Sandstones  a Late Albian  age has  been  recognized. These  new data  would suggest  an older Cretaceous  age  for the beginning of the Corsican flysch deposition  (Albian-Cenomanian) when compared to the Santonian and  Maastrichtian  ages of the Cretaceous  flysch  in the Northern  Apennine. These results  concerning  the age of Corsican  flysch together with  the stratigraphic-structural  and sedimentological  data from the literature,  provide  new interesting considerations  about  the paleogeography of western Tethys.